UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA PEMAHAMAN PADA PESERTA DIDIK KELAS IV DI SD NEGERI BABAKAN KABUPATEN TANGERANG - Puspa Astita; Mujazi Mujazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore in depth the efforts made by teachers in overcoming reading comprehension difficulties in grade IV students at SD Negeri Babakan, Tangerang Regency. Given the important role of reading comprehension in academic success, this study uses a qualitative approach with a descriptive method. Data were obtained through in-depth interviews with the principal, teachers, and students, as well as direct observation during learning and analysis of related documents. The findings of the study indicate that teachers apply various strategies to overcome difficulties in reading comprehension. These strategies include the use of text-based learning methods that are appropriate to the level of students' abilities, the application of interactive techniques such as group discussions, and individual approaches to address specific difficulties faced by each student. In addition, teachers also conduct regular formative evaluations to monitor the development of students' reading comprehension. These findings indicate that an approach that is tailored to the individual needs of students and collaboration with parents can improve the effectiveness of the reading learning process. This study recommends the need for more in-depth training for teachers on innovative and adaptive reading teaching strategies to address various challenges in students' reading comprehension.